The study of the aircraft navigation systems: radio navigation system as a model / Ahmad Nazri Nasir and Ruszaini Ariffin - Nasir, Ahmad Nazri; Ariffin, Ruszaini (2000)
The study that has been conducted in this project paper is treated about the principles and the design concepts of navigation systems. Most of the chapters discussed are concerning only about the civil aviation and none of the topics is exclusively military. The subject matter is complex and wide-ranging hence not all aspects can be covered in one volume. This project paper is concerned with more on theory and general knowledge of design concepts and also little else that this is not may be so clear if we outline briefly the contents of each chapters. An introduction saying a few words about the general information of navigation systems. The next two chapters are discussed about the requirement and design characteristics of the navigation systems are followed by a fairly thorough coverage of the fundamentals and the navigation system itself. The other chapters are a briefly look at the principles and operations of the radio navigation systems and its sub-systems to break up the flow of the more theoritical aspects. At the end of the project, we did the conclusion on what we have been discussed on overall topics and also closes a section on developmental trends for the mcoming years which will produce exciting new devices and systems for navigation that provide the navigator with capabilities never before dream of. These are all about the project that present the principles and design characteristics of modern aircraft navigation systems and it is hoped that this project will disseminate the fundamentals and significant fact related to devices and systems in order to further the practical use and stimulate innovation development toward improving systems of navigation.